Techniques for alarm management with fault diagnostic system in startups and shutdowns for industrial processes - Vasquez Capacho, Jhon William; Mayorga, Manuel Alejandro; Cortez, Alexander; Bernal, V; Bustos, Alvaro (TECCIENCIA, 2014)
This paper presents a preliminary study of the different techniques that can be used for fault diagnostics in industial processes specially on the startup and shutdown procedures. A review of these thecniques from the perspective of how its can be used for Alarm management is presented, followed by an analisys of fault diagnostic in complex systems passing techniques like the causal graph. Another technique exposed is the use of chronicles as a robust method for fault diagnosis; in a first part we examine aspects as diagnostic, Timed Diagnosability, then propose an automated translation of chronicles, and how it can be used on the alarm management in a starting or shutdown plant. Concluding with a preliminar methodolgy propoused that includes the use of tha causal graph with the chronicles in an Alarm management.